Usulan Perbaikan Sistem Antrian menggunakan Software Simulasi Arena pada Pelayanan Poli Gigi Puskesmas Gamping 1 - Fana Fitriah; Bayu Jatnika; Nor Alvia Hidayati; Dinar Mahar Ghany; Peri Indrawan; Angga Wira Rizki; Sido Dea Auvia (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2026)
The high volume of queues in public health services directly threatens service quality and patient satisfaction. At the Dental Clinic of Puskesmas Gamping 1, the surge of patients, especially on busy days such as Saturday, causes the ratio of waiting time to service time to increase significantly, indicating serious inefficiencies in the system. The urgency of this research is to design an optimal and sustainable queuing system to break the cycle of long queues and patient complaints. This study aims to analyze, evaluate, and optimize the efficiency of the queuing system of the Dental Clinic of Puskesmas Gamping 1. The research method used is computer-based discrete simulation (Discrete Event Simulation). Queuing data and service time were collected through direct observation and processed using the distribution test. Valid data is then modeled in Arena software. The simulation model was validated and verified to reflect real conditions. Next, two improvement scenarios were developed: (1) adding one registration officer and (2) adding one service officer. The simulation results show that the existing system has an average waiting time of 35.4 minutes. The best improvement scenario was Scenario 2 with the addition of one service officer, which significantly reduced patient waiting time by 60% to 14.2 minutes. In conclusion, Arena simulation is an effective tool for Puskesmas queuing system optimization. Recommendations for the implementation of the best scenario are expected to improve the efficiency and quality of services at the Dental Clinic of Puskesmas Gamping 1.